Mixed-quantum-dot solar cells. Issue 1 (December 2017) - Yang, Zhenyu; Fan, James; Proppe, Andrew; Arquer, F. Pelayo García de; Rossouw, David; Voznyy, Oleksandr; Lan, Xinzheng; Liu, Min; Walters, Grant; Quintero-Bermudez, Rafael; Sun, Bin; Hoogland, Sjoerd; et al.
Abstract Colloidal quantum dots are emerging solution-processed materials for large-scale and low-cost photovoltaics. The recent advent of quantum dot inks has overcome the prior need for solid-state exchanges that previously added cost, complexity, and morphological disruption to the quantum dot solid. Unfortunately, these inks remain limited by the photocarrier diffusion length. Here we devise a strategy based on n- and p-type ligands that judiciously shifts the quantum dot band alignment. It leads to ink-based materials that retain the independent surface functionalization of quantum dots, and it creates distinguishable donor and acceptor domains for bulk heterojunctions. Interdot carrier transfer and exciton dissociation studies confirm efficient charge separation at the nanoscale interfaces between the two classes of quantum dots. We fabricate the first mixed-quantum-dot solar cells and achieve a power conversion of 10.4%, which surpasses the performance of previously reported bulk heterojunction quantum dot devices fully two-fold, indicating the potential of the mixed-quantum-dot approach. Solution processed colloidal quantum dots are emerging photovoltaic materials with tuneable infrared bandgaps. Here, Yang et al. create a class of quantum dot bulk heterojunction solar cell via ligand design, enabling longer photocarrier diffusion lengths for greater photocurrent and performance.